Piezo1 controls cell volume and migration by modulating swelling‐activated chloride current through Ca2+ influx. Issue 3 (15th December 2021) - Sforna, Luigi; Michelucci, Antonio; Morena, Francesco; Argentati, Chiara; Franciolini, Fabio; Vassalli, Massimo; Martino, Sabata; Catacuzzeno, Luigi
Abstract: Regulatory volume decrease (RVD), a homeostatic process responsible for the re‐establishment of the original cell volume upon swelling, is critical in controlling several functions, including migration. RVD is mainly sustained by the swelling‐activated Cl − current (ICl, swell ), which can be modulated by cytoplasmic Ca 2+ . Cell swelling also activates mechanosensitive channels, including the ubiquitously expressed Ca 2+ ‐permeable channel Piezo1. We hypothesized that, by controlling cytoplasmic Ca 2+ and in turn ICl, swell, Piezo1 is involved in the fine regulation of RVD and cell migration. We compared RVD and ICl, swell in wild‐type (WT) HEK293T cells, which express endogenous levels of Piezo1, and in cells overexpressing (OVER) or knockout (KO) for Piezo1. Compared to WT, RVD was markedly increased in OVER, while virtually absent in KO cells. Consistently, ICl, swell amplitude was highest in OVER and lowest in KO cells, with WT cells displaying an intermediate level, suggesting a Ca 2+ ‐dependent modulation of the current by Piezo1 channels. Indeed, in the absence of external Ca 2+, ICl, swell in both WT and OVER cells, as well as the RVD probed in OVER cells, were significantly lower than in the presence of Ca 2+ and no longer different compared to KO cells. However, the Piezo‐mediated Ca 2+ influx was ineffective in enhancing ICl, swell in the absence of releasable Ca 2+ from intracellular stores. The different expression levels of Piezo1 affected also cell migration which was strongly enhanced in OVER, while reduced in KO cells, as compared to WT. Taken together, our data indicate that Piezo1 controls RVD and migration in HEK293T cells by modulating ICl, swell through Ca 2+ influx. Abstract : Piezo1 enhances both the hypotonic‐induced RVD and the migratory capacity of HEK293T cells by increasing the activity of ICl, swell  through the entry of extracellular Ca 2+ .